DAMPAK PERUBAHAN IKLIM TERHADAP PRODUKTIVITAS PADI DI PULAU JAWA DI MASA MENDATANG - Nazarudin, Leni (Jurnal Widya Climago, 2024)
Using the climate projection data from the ensemble model output from the CORDEX-SEA (Coordinated Regional Climate Downscaling Experiment-South East Asia) grid-based (25 km x 25 km) project in Java (205 grids), a simulation of growth and production of rice was carried out using the AquaCrop FAO model (AquaCrop64bit version 5.0). The climate projection data is an ensemble of 6 models: CNRM-CM5, CSIRO-MK3.6, EC-EARTH, GFDL-ESM2M, IPSL and MPI-ESM-MR consisting of a 30-year period data: historical data for the period 1976-2005, RCP4.5 scenario for the 2020-2049 period and RCP8.5 scenario data for the 2020-2049 period in the form of daily rainfall data, maximum temperature, average temperature and minimum temperature. AquaCrop simulation uses climate and soil texture data variables with irrigation sources from rainwater. This study aims to determine the impact of climate change on rice productivity in Java as the changes in rice productivity in Java in the near future period (2020-2049) against the historical period (1976-2005) using RCP4.5 and RCP8.5 scenarios in the months of rainy season, dry season and transition seasons.. Climate change has an impact on increasing rice productivity 0-30% in the rainy season months throughout Java and in the dry season months it has an impact on reducing rice productivity 60-90% with a high emission scenario (RCP8.5) in rice production centers in coastal areas north of West Java, middle Java and the center of rice production in East Java. This condition can threaten national food security in the future.